Perlindungan Hukum terhadap Pemegang Saham Minoritas yang Dirugikan Akibat Dilusi Saham: Analisis Putusan Pengadilan - Raden Aditya Barkah Nugraha; Sodikin Sodikin; Sawitri Yuli Hartati S. (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2026)
This study aims to critically analyze judicial legal reasoning at various levels of adjudication, including district court, high court, cassation, and judicial review by the Supreme Court, in interpreting the legal protection of minority shareholders affected by share dilution. This research employs a normative legal method with a qualitative approach, relying on the analysis of court decisions, statutory regulations, and corporate law doctrines. The findings indicate that although Article 62 of the Indonesian Company Law constitutes an imperative norm oriented toward substantive protection, its application in the judicial review decision tends to be formalistic and disregards power imbalances inherent in corporate ownership structures. Such an approach ultimately weakens legal certainty and undermines minority investor protection within Indonesia’s corporate legal system.